Pseudoseptic Reaction to an Intra-Articular Polydeoxyribonucleotide Injection into the Ankle: A Case Report - Seungcheol Yu; Hangaram Kim; Youngwoong Choi; Jeongsoo Kim (International Journal of Pain, 2024)
Pseudoseptic arthritis is a rare complication mimicking septic arthritis following intra-articular injections. While hyaluronic acid (HA) has been the primary agent linked to such reactions, we report a case of pseudoseptic arthritis after polydeoxyribonucleotide (PDRN) injection in an 81-year-old male with bilateral ankle osteoarthritis. Severe left ankle pain, swelling, and fever developed seven days after the second PDRN injection, with elevated inflammatory markers. Synovial fluid analysis revealed no infectious organisms or crystals, and septic arthritis was ruled out through synovial fluid cultures. Pseudoseptic arthritis was diagnosed. This case suggests that pseudoseptic arthritis may arise not only with HA but also with PDRN, emphasizing the need to be aware of this complication with other injection agents.